Ultralow surface recombination velocity in InP nanowires probed by terahertz spectroscopy. - Joyce, H; Wong-Leung, J; Yong, C; Docherty, C; Paiman, S; Gao, Q; Tan, H; Jagadish, C; Lloyd-Hughes, J; Herz, L; Johnston, M (2012)
Using transient terahertz photoconductivity measurements, we have made noncontact, room temperature measurements of the ultrafast charge carrier dynamics in InP nanowires. InP nanowires exhibited a very long photoconductivity lifetime of over 1 ns, and carrier lifetimes were remarkably insensitive to surface states despite the large nanowire surface area-to-volume ratio. An exceptionally low surface recombination velocity (170 cm/s) was recorded at room temperature. These results suggest that InP nanowires are prime candidates for optoelectronic devices, particularly photovoltaic devices, without the need for surface passivation. We found that the carrier mobility is not limited by nanowire diameter but is strongly limited by the presence of planar crystallographic defects such as stacking faults in these predominantly wurtzite nanowires. These findings show the great potential of very narrow InP nanowires for electronic devices but indicate that improvements in the crystallographic uniformity of InP nanowires will be critical for future nanowire device engineering.